Design and implementation of power efficient image compressor for WSN systems. (2021) - Krishnamoorthy, Raja; Jayasankar, T.; Shanthi, S.; Kavitha, M.; Bharatiraja, C.
Abstract: In the digital electronics era, video and image processing, storage, data transmitting, data streaming, data retrieval, video playback features increasing exponentially. These requirements data processing and storage improvement results to necessity of hybrid compression, efficient encoding and decoding, compression ratio techniques in demand for modern real time applications. For that spatial domine technology of compression is prefer to satisfy the computational constraint for real time gadgets. Discrete wavelet transformation (DWT) based Multi-Level Block Truncation Coding (MLBTC) methodology used for special domine. Discrete Wavelet Transform procedure is utilized to constant and motion images and implemented to all mean pixel estimation of the image. Loss type compression technology BTC is implemented for gray scale image processing. It designed that original image divided as square blocks with help of quantize for decrease the gray intensity images every portion of square box having equal standard deviation and Mean values. In this proposed methodology is analysis of BWT-MLBTC image compression technologies for both binary and color images. The methodology has been implemented in Xilinx ISE software, the simulation results shows that the proposed method consumes less hardware resources, delay generations and power utilizations compared to the state of art approaches.